Explicating meanings of counterfeit branded fashion goods consumption through phenomenological lens among young adult consumers - Rosely, Nurhidayah (2021)
This thesis explored the meaning of counterfeit consumption activity, as well as how this consumption practice fulfilled the psychological needs and life goals pursuits of young adult consumers from the interpretive point of view. Consumption experiences of 12 consumers gathered through in-depth interviews were analysed. Essentially, this study focused on the purchase of counterfeit branded fashion goods, wherein the rising demand for counterfeit goods has led to a new phenomenon in consumer behaviour. The phenomenology approach was adapted to uncovered rich and contextualised account of consumer consumption experiences, which elucidated a range of meanings on consumers’ involvement in counterfeit consumption, namely price worth, comparable quality, seems identical, unavailability, compensating original brand, prized collection, and special occasion. These various meanings of counterfeit consumption reflect both self-image and identity held by each consumer in relation to their existential concerns and social contexts. The three categories that emerged from the themes; branded value buy, satisficing wants, and sacred consumption, highlighted the significance of branded fashion goods to the consumers. The outcomes drawn from research objectives (ROs) and research questions (RQs) two and three unravelled the role of counterfeit consumption in fulfilling psychological needs and pursuing life goals of the consumers. The following emerging themes; sharing information, trusted sources, social learning, society norms, fear of being exposed, adept, deceiving, discernment, dedicated, and satisfaction, were classified into four categories of psychological needs fulfilment, namely: social capital, social acceptance, competent consumer, and self-interest. The consumers’ experiences in counterfeit consumption yielded the following themes; need to be different, showing off, inadequacy, and keeping up with the trends, which were further classified into two categories, namely conspicuous and materialism. This classification sheds light on the contribution of extrinsic life goals to hedonic well-being and life happiness. The findings derived from all RQs and ROs were illustrated through the lens of Cognitive Dissonance Theory (CDT) and Self-Determination Theory (SDT), which guided the construction of themes and categories in the thematic analysis process, thus deciphering the meaning of counterfeit consumption and its role in satisfying consumers’ psychological needs and well-being through extrinsic life goals. As the phenomenology approach only probed into the living experience of consumers involved in counterfeit branded fashion goods consumption, in which the consumers were selected via purposive and snowball sampling, this study dismissed age diversity of the consumers. Besides, the issue at hand was rather sensitive and required the consumers to reveal their unethical and illegal consumption practice. This study selected consumers of Generation Z (Gen Z) and Millennials with similar background and operationalised as young adult consumers. Hence, this study does not claim to have developed an exhaustive account of counterfeit consumers. Essentially, this study contributes knowledge in the areas of counterfeit branded fashion goods and consumer behaviour with the discovery of the following new emergent categories; branded value buy, sacred consumption, social capital, and social acceptance. They describe the actual experiences captured from the consumers, who were continuously involved in counterfeit consumption practice. This thesis contributes to scholarly and managerial knowledge from the hedonic and experiential dimensions in the Malaysian context, which sheds light on the underlying causes of counterfeit consumption phenomena.